1989
DOI: 10.1172/jci114096
|View full text |Cite
|
Sign up to set email alerts
|

RNA fingerprinting of respiratory syncytial virus using ribonuclease protection. Application to molecular epidemiology.

Abstract: We have used the technique of ribonuclease protection to define genomic variation among circulating isolates of subgroup A respiratory syncytial (RS) virus. RNAs extracted from HEp-2 cells infected with strains to be analyzed were hybridized with a 32P-labeled RNA probe corresponding to the RS virus G glycoprotein (A2 strain). Areas of nonhomology were detected by cleavage with ribonuclease A. Using this technique, multiple distinct RNA cleavage patterns could be distinguished among viral isolates recovered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…It appears that the comparative sequencing of RS virus subgroup A strains published so far has been carried out fortuitously on closely related strains, so giving a distorted impression of the degree of relatedness between strains within subgroup A. This view is supported by studies using ribonuclease protection experiments which also suggest that much greater diversity is present in clinical isolates than might be inferred from consideration of the published F and P data alone (Storch et al, 1989;Cristina et al, 1990). In addition these ribonuclease protection studies show that some strains, apparently closely related in terms of fragment pattern, could reappear some years later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the comparative sequencing of RS virus subgroup A strains published so far has been carried out fortuitously on closely related strains, so giving a distorted impression of the degree of relatedness between strains within subgroup A. This view is supported by studies using ribonuclease protection experiments which also suggest that much greater diversity is present in clinical isolates than might be inferred from consideration of the published F and P data alone (Storch et al, 1989;Cristina et al, 1990). In addition these ribonuclease protection studies show that some strains, apparently closely related in terms of fragment pattern, could reappear some years later.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of very limited numbers of RS virus strains within subgroup A indicate less diversity: 94~ amino acid identity for the G protein (Johnson et al, 1987), 97 to 98 9/0 for the fusion (F) protein (Baybutt & Pringle, 1987;Scopes et al, 1990), 98 ~ for the 22K protein (Baybutt & Pringle, 1987), 98 to 99~ for the phosphoprotein (P) (Lambden, 1985;Lopez et al, 1988) and 100~ for the N protein (Johnson & Collins, 1989). In addition, MAb and ribonuclease protection studies have suggested that there may be heterogeneity within subgroup A (Garcia-0000-9817 © 1991 SGM Barreno et al, 1989;Hendry et al, 1989;Storch et al, 1989;Cristina et al, 1990). However, a deficiency of both MAb and ribonuclease protection studies is that they use only one or a small number of previously isolated strains for MAb or cDNA clone production, and as the reference point in comparative studies.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have used MAbs to assess intragroup antigenic variability; HRSV strains of both groups were assigned to different antigenic subgroups, on the basis of their reactivity patterns with panels of MAbs [Storch et al, 1991]. Other methods have been used to evaluate genetic diversity within groups, such as Rnase A fingerprinting [Storch et al, 1989;Cristina et al, 1990], restriction endonuclease digestion Cane et al, 1992;Coggins et al, 1998;Choi and Lee, 2000], and/or nucleotide sequencing [Peret et al, 1998;Roca et al, 2001;Venter et al, 2001]. These studies have confirmed the extensive genetic diversity of the G gene between and within HRSV groups and have also shown the occurrence of several evolutionary lineages or genotypes with worldwide distribution [reviewed by Melero et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition to the diversity present between the 2 major subgroups, there is evidence of variability within each of the subgroups. 1,4,11,13,14,29,30 Ruminant RSV isolates include viruses from cattle, sheep, and goats suffering from lower respiratory tract infection. 5,17,18,27 Bovine RSV is a major cause of respiratory disease in cattle and shares many similarities with human RSV with respect to epidemiologic patterns, clinical disease, immunologic response, and pathologic features.…”
mentioning
confidence: 99%